2021
DOI: 10.1038/s41598-021-85771-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 5-day dry immersion on the human foot morphology evaluated by computer plantography and soft tissues stiffness measuring

Abstract: Abstract16 participants have been subjected to Dry Immersion model (DI) for 5 days. DI reproduces the space flight factors such as lack of support, mechanical and axial unloading, physical inactivity, elimination of vertical vascular gradient. Long-term bed rest is also associated with similar factors, so the results of the study may be useful for clinical medicine. Computer plantography and measuring the stiffness of the soft tissues of the foot and superficial muscles of the shin (mm. tibialis anterior and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
1
0
0
Order By: Relevance
“…Moreover, a study of muscle tone in a long-term 21-day DI showed a decrease in the tibialis anterior muscle and an increase in the soleus and gastrocnemius muscles, which may be the result of functional compensation through increasing fascial contractility ( Amirova et al, 2020 ). A similar phenomenon was also observed in a study of the dynamics of the morphological and functional characteristics of the foot structure in a 5-day DI ( Saveko et al, 2021 ), as well as in the rectus femoris muscle in a 3-day DI ( Demangel et al, 2017 ). Furthermore, Reschke et al (2009) noted a decrease in the stretch reflex parameters of the postural muscles after exposure to long-duration head-down bed rest: a decrease in start latency and peak latency of the monosynaptic stretch reflex, peak magnitude and latency of the functional stretch reflex ( Reschke et al, 2009 ).…”
Section: Dry Immersionsupporting
confidence: 80%
“…Moreover, a study of muscle tone in a long-term 21-day DI showed a decrease in the tibialis anterior muscle and an increase in the soleus and gastrocnemius muscles, which may be the result of functional compensation through increasing fascial contractility ( Amirova et al, 2020 ). A similar phenomenon was also observed in a study of the dynamics of the morphological and functional characteristics of the foot structure in a 5-day DI ( Saveko et al, 2021 ), as well as in the rectus femoris muscle in a 3-day DI ( Demangel et al, 2017 ). Furthermore, Reschke et al (2009) noted a decrease in the stretch reflex parameters of the postural muscles after exposure to long-duration head-down bed rest: a decrease in start latency and peak latency of the monosynaptic stretch reflex, peak magnitude and latency of the functional stretch reflex ( Reschke et al, 2009 ).…”
Section: Dry Immersionsupporting
confidence: 80%